Effective Utilization of Granulated Blast Furnace Slag as AFine Aggregate Replacement In The Study of Mechanical Properties of Concrete - Mohit Verma, Hemant Singh Parihar (International Journal of Advanced Science and Technology, 2020)
This study investigates the effective utilization of Granulated Blast Furnace Slag (GBFS) along fine aggregate (FA) replacement with concrete structures to reduce its adverse environmental impacts. GBFS was used as fine aggregate in place of natural sand (NS) in concrete. Design mix of M30 grade of concrete with water cement ratios of 0.40 was used with the percentage replacement of 0%, 10, 30, 50, 70 and 100%. It was observed from the results indicates the partial utilization of GBFS with 50% as different construction material in place of NS in concrete structures. Reduction in workability measured by slump test was maintained by cast appropriate percentage of super